2021
DOI: 10.1186/s12879-021-06208-2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of SARS-CoV-2 IgG seroconversionamong front-line healthcare workers during the first wave of the Covid-19 pandemic at a tertiary-care hospital in Chile

Abstract: Background Healthcare workers (HCWs) are at high risk of exposure to SARS-CoV-2. Cross-sectional studies have provided variable rates of seroprevalence in HCWs. Longitudinal assessments of the serological response to Covid-19 among HCWs are crucial to understanding the risk of infection and changes in antibody titers over time. We aimed to investigate seroprevalence and risk factors associated with seroconversion in a prospective cohort of HCWs during the peak of the first wave of the Covid-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 38 publications
6
29
2
1
Order By: Relevance
“…In a study conducted on the general population from March to July 2021, 5-9 months following our data collection, 3,726/59,987 (6.2%) reported a previous PCR positive result and seropositivity by anti-SARS-COV-2 finger prick testing (only IgG) reached 18% among non-vaccinated individuals [22] . A study focusing on frontline HCWs from a tertiary-care hospital in Santiago, conducted from April- July of 2021, found a much higher seroprevalence of 24% (n=446) [23] compared to 12% of HCWs in Santiago in our study. This may be due to the inclusion of only frontline workers, and/or the use of a more sensitive antibody detection method (importantly we report that the test used in our study detected nearly 50% of known PCR positive cases).…”
Section: Discussioncontrasting
confidence: 47%
“…In a study conducted on the general population from March to July 2021, 5-9 months following our data collection, 3,726/59,987 (6.2%) reported a previous PCR positive result and seropositivity by anti-SARS-COV-2 finger prick testing (only IgG) reached 18% among non-vaccinated individuals [22] . A study focusing on frontline HCWs from a tertiary-care hospital in Santiago, conducted from April- July of 2021, found a much higher seroprevalence of 24% (n=446) [23] compared to 12% of HCWs in Santiago in our study. This may be due to the inclusion of only frontline workers, and/or the use of a more sensitive antibody detection method (importantly we report that the test used in our study detected nearly 50% of known PCR positive cases).…”
Section: Discussioncontrasting
confidence: 47%
“…Numerous previous reports have described cross-sectional seropositivity in HCWs during the earliest phases of the pandemic, from early to mid-2020 [ 1 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 21 ]. One systematic review that included studies from the start of the pandemic through August 2020 reported roughly similar overall seropositivity among HCWs across the globe of 8.7% (95% confidence interval 6.7–10.9%) with seropositivity of 12.7% (95% confidence interval 8.6–17.5%) in North America; rates in varied settings ranged from 0% to 45.3% in the sampled studies [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, prior serosurvey studies focusing on HCWs (including clinical and non-clinical workers) have not reported how SARS-CoV-2 seropositivity evolved over an extended period during the early phases of the pandemic. To date, we found only two studies that describe seroconversion trends for HCWs—however, both were limited to a duration of one to two months [ 14 , 15 ]. In addition, most studies have not contextualized the observed seropositivity rates of HCWs with the seropositivity and/or positive test rates in the local community, despite this being a large source of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Among the health professionals who worked during the pandemic, women represented the largest proportion—they also being the ones that perform the major care functions at home. Even in different studies carried out in Latin American countries, women constituted the highest proportion: Chile (72.6%) [ 37 ], Ecuador (68.3%) [ 38 ], Argentina (71%) [ 39 ], Bolivia (72.9%) [ 40 ], and Peru (71%) [ 41 ]. According to the United Nations Entity for Gender Equality and the Empowerment of Women [ 36 ], 70% of the global health workers are women (eg, nurses, midwives, community health workers) also working as cleaners, caterers, and launderers in health facilities; they have few leadership positions (30%) and lower salaries.…”
Section: Discussionmentioning
confidence: 99%